PERANCANGAN MEDIA PROMOSI WISATA TANJUNG PAPUMA GUNA MENINGKATKAN BRAND AWARENESS - Prasetya, Mahardika; Fianto, Achmad Yanu Alif; Karsam, Karsam (Jurnal ArtNouveau, 2013)
Tourist area of ââTanjung Papuma not been promoted effectively to the public through the media that is still a lot of tourists who do not know about the existence of Tanjung Papuma tour. In terms of the physical, natural conditions Tanjung Papuma still fairly original and the attributes possessed Tanjung Papuma also diverse, in addition to presenting the beauty of the tourist beaches of Tanjung Papuma also has an array of beautiful hills, coupled with the unique diversity malikan stone. Has a natural blend of the exotic makes leading tourist spot in Jember is ready for sale civic. Tourism Cape Papuma included in the category of ecotourism, which is a concept of nature that are relatively still not disturbed or contaminated (polluted) with the aim of studying, admiring and enjoying the scenery, vegetation and wildlife, as well as other forms of cultural manifestations that there. In order for this tour visited by tourists we need a proper tourism promotion strategy and integrated so many local and outside people who know and are willing to travel to Cape Papuma sights. In making the design of effective tourism promotion media then conducted analyzes to address research problems of the public perception of nature, particularly the nature beach in Tanjung Papuma, the selection of the target audience, market segmentation and classification of the research output of the media campaign that will be used. The achievement will be concluded to get the proper visual and marketing in accordance with market potential